CLINICAL EVALUATION OF THERAPEUTIC EFFECT OF HARIDRA (CURCUMA LONGA L.) IN THE MANAGEMENT OF WOUND HEALING (AYUSHDHARA, 2017)
Wound is common problems from ancient time. Wound is simply a disruption of any tissues: soft tissue or bone or internal organs. Wound may be produced by physical, chemical, thermal, microbial or immunological insult to the tissue. Although wound healing is a natural restorative response to any kind of tissue injury but due to bacterial contamination of an open wound delays the process of healing. Therefore the aim of treating a wound is to either shorter the time required for healing or to minimize the undesired consequences. In present study 16 patients with classical signs and symptoms of wound were randomly selected in OPD/IPD of govt. Ayurved Hospital Patna. The fine powder and decoction of Haridra were prepared. Decoction applied externally for dressing the wound and 3gm. fine powder given orally twice a day for 30 days. The area of wound measured manually by tracing methods. The values of scores of different variables i.e. signs & symptoms recorded before & after the treatment were statistically analyzed. It is observed that the size, pain, tenderness, swelling, discharge, burning sensation, and colour of wound all were decreased with statistically highly significant value at the level (P< 0.001). The study shows that Haridra having excellent properties to accelerate the wound healing safely.